1 Del. Laws 104 (1797) - (:unkn) unknown (My University, 1797)
Ch. 43, § 6: Prohibited "any Negro or Mulatto slave" from carrying guns, swords, pistols, fowling pieces, clubs, or other arms and weapons without the master's special license.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES